The convergence of the traditional sociomedical and the contemporary biomedical paradigms: is it possible? (Revista Venezolana de Salud Pública, 2019)
This essay lays out some thoughts regarding the social healing practices that coexist with scientific Medicine in Venezuela, pursuant towhat has been expressed by expert doctors, young specialist doctors and users of the healthcare services in the Socialist Venezuela of the21 st century. The interest of such research focused on interpreting with a critical spirit the meanings of the medical discourse regarding thecharacteristics of scientific and pre-scientific medicine, as well as the users’ experiences who combined scientific medicine withtraditional medicine practices in the search for a solution to their health problems. I took the critical analysis of discourse described byTeun Van Dijk as core of the investigation. I found differences between medical voices: While expert doctors centered their attention onthe importance of scientific Medicine, its achievements, challenges and contradictions, thinking about the need to apply scientificmedicine in order to reveal truths hidden by traditional practices, young doctors focused their attention on the supremacy of scientifictraining during medical education, the discrimination suffered by traditional healing practices under medical training and medicalpractice, as opposed to the frequent use of traditional healing practices in the rural and urban populations they have assisted. Theconcerns expressed by users of the healthcare services revealed a complementary coexistence of Medicine and traditional practices. Toconclude, the horizons of change that might a complementary coexistence be useful for the reconstruction of the Healthcare System inVenezuela were presented: Critical & Theoretical Integration of the Contemporary Biomedical and Traditional Sociomedical Paradigmsfrom an interdisciplinary point of view.
Keywords: traditional medicine; scientific medicine